2016
DOI: 10.1017/s0030605315001477
|View full text |Cite
|
Sign up to set email alerts
|

Are we working to save the species our children want to protect? Evaluating species attribute preferences among children

Abstract: As conservation resources decline and numbers of threatened species increase, prioritizing species for conservation is increasingly important, and prioritizing based on attributes may be the most efficient approach. Despite the importance of biodiversity as a legacy to future generations, children's preferences for species attributes have never been considered. We surveyed 3rd and 5th grade students, typically 8–10 years old, in North Carolina, USA, to determine how children prioritize conservation of species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…Interpreting patterns of heightened local interest in endangered species also presented challenges. Multiple studies have shown that people assign greater value to species in need of conservation (11,20,21); however, it is also clear that protected species may attract attention for a variety of reasons (22).…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting patterns of heightened local interest in endangered species also presented challenges. Multiple studies have shown that people assign greater value to species in need of conservation (11,20,21); however, it is also clear that protected species may attract attention for a variety of reasons (22).…”
Section: Discussionmentioning
confidence: 99%
“…Boys tend to favour animals that evoke fear and disgust over girls, and girls prefer more loveable or cute animals (Prokop & Tunnicliffe 2010; Schlegel & Rupf 2010). Children appear to prioritize species groups in ways that are similar to conservation biologists by prioritizing importance in nature over other attributes (Frew et al 2016; Shapiro et al 2016), whereas adults may place more emphasis on endemism and declining species (Czech et al 1998; Meuser et al 2009; Verissimo et al 2009). Although importance in nature is necessarily a general concept, children tend to view it as referring to a species’ overall significance and value to the natural system in which it resides (Shapiro et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our results that younger students included more local animals as liked (sixth graders) and fewer as scary (fourth graders) than other grade levels could be related to curriculum (e.g., both sixth and fourth grades have wildlife-related standards: NC Department of Public Instruction, ). However, other studies find that connections to nature and interest in the environment and wildlife decline as children age (Frew, Peterson & Stevenson, 2016; Stevenson et al, 2013), suggesting that efforts should continue to find ways to engage with older children. Finally, Caucasian children listed more local species for both liked and scary animals, suggesting a higher level of familiarity with local wildlife.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to the extent that megafauna are often not only threatened, but also conservation targets (Dietz, Dietz & Nagagata, 1994; Smith & Sutton, 2008), the fondness of children for “loveable animals” may actually lead to a fondness for species of conservation concern. One recent study even showed potential for children to align more closely with conservationists’ prioritization of species attributes (Frew, Peterson & Stevenson, 2016) than adults in a similarly designed study (Meuser, Harshaw & Mooers, 2009).…”
Section: Introductionmentioning
confidence: 99%